The Usage of Surface Distress Index (SDI) and Pavement Condition Index (PCI) to Evaluate The Condition of Jamin Ginting National Road (BTS. Medan City - BTS. Karo Regency) - Brahmana, Ivana Christine Sembiring; Hasibuan, Gina Cynthia Raphita; Anas, Muhammad Ridwan (ASTONJADRO, 2024)
Considering the importance of national roads, it is necessary to conduct a review of maintenance strategies based on Minister of Public Works Regulation No. 13/PRT/M/2011 where road maintenance is a road handling activity, in the form of prevention, maintenance and repairs needed to maintain the condition of the road so that it continues to function optimally and serve the road so that the specified life plan can be achieved. The results of research carried out using the Pavement Condition Index (PCI) method for the Bts direction. Medan City – Bts. Regency. Karo is in "Good" condition and the strategy for maintenance is Routine Maintenance along 5.8 Km, Preventive Maintenance along 1.6 Km, Rehabilitation along 0.9 Km, Major Rehabilitation along 1.7 Km at IDR 5,278,395,170.